2021
DOI: 10.1080/21655979.2021.2000789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microscopic testa color and morphologyon the water uptake ability and drought tolerance of germination-stage rapeseed (Brassica napus L.)

Abstract: Drought is one of the most important abiotic stressors that affect crop yield. Therefore, the aim of the present study was to investigate correlations between germination-stage drought tolerance and the microscopic testa (i.e., seed coat) characteristics (color and papilla morphology) and imbibition abilities of 35 rapeseed ( Brassica napus L.) accessions. After 2 h imbibition, seed water uptake (fresh weight increase) was significantly positively correlated with testa hue ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In accordance with Moncaleano-Escandon [21], the deterioration process begins with the loss of selective permeability of the cellular membranes and ends with the loss of the germination capacity. Water is distributed in crevices, cracks, and flaws in the seed cover, and is absorbed by the seed tissues [44]. Water-uptake measurements, taken during this phase have shown these rates to be: (1) temperature-dependent; and (2) accompanied by increases in respiration rate and in light sensitivity in some seed species [21,25,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with Moncaleano-Escandon [21], the deterioration process begins with the loss of selective permeability of the cellular membranes and ends with the loss of the germination capacity. Water is distributed in crevices, cracks, and flaws in the seed cover, and is absorbed by the seed tissues [44]. Water-uptake measurements, taken during this phase have shown these rates to be: (1) temperature-dependent; and (2) accompanied by increases in respiration rate and in light sensitivity in some seed species [21,25,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In direct‐seeding rice, rapid seed germination and vigorous seedling growth are essential for achieving high crop yield (He, Yang, et al., 2019). Drought stress is particularly detrimental to seed germination, leading to delayed seedling establishment in dry direct‐seeded rice (He et al., 2021; Zheng et al., 2016). Therefore, studying the natural variation and genetic mechanisms underlying drought tolerance during germination can contribute to the genetic improvement of rice growth and grain yield.…”
Section: Introductionmentioning
confidence: 99%
“…B. napus is not only valuable as a vegetable and an edible oil [23], but can also be used for ornamental purposes, as a source of nectar, in the remediation of heavy metal pollution and as an industrial raw material crop [24,25]. Moreover, B. napus cake contains higher protein, making it suitable for use as high-quality feed, with a positive impact on promoting and developing the breeding industry [24][25][26][27]. Zhao et al (2019) found that B. napus rotation can increase the nutrient content of the soil and improve the biological characteristics of the soil, thereby increasing the yield of subsequent crops and contributing to the green and sustainable development of agriculture [28].…”
Section: Introductionmentioning
confidence: 99%